Smart City as Urban Innovation Management Practice - Prasad Pathak, Deepali Shahane, Ms. Gunjan Behl, Mr. Alok Shah, Shambhu Shankar Rai (Mathematical Statistician and Engineering Applications, 2023)
This paper views a smart city as an effort by a city to become smarter than it already is. A smart city is a metaphor for urban innovation in management, public policy, and technology. A smart city can be thought of as a contextualized interaction between technical innovation, managerial and organizational innovation, and policy innovation. This is because each city has a certain environment that determines its technological, organizational, and policy features. However, whereas there is a wealth of literature on technological innovation, little research has been done on innovation in management and policy. It is customary to bring up a new stage of urbanization, the establishment of smart cities, while talking about the topic of urban area development.Nowadays, more and more cities are described as "intelligent" or "smart," despite the lack of a precise definition that would outline the requirements that cities must satisfy to be classified in this way. The existing sets of criteria are quite unclear and vary in importance based on the geography, among other things. Determining whether, to what extent, and for what reasons cities may be deemed smart cities is thus immensely essential and valuable. The article's goals are to first determine the extent to which the smart city idea is employed to manage cities generally and, second, to determine whether it is possible to lower operating costs for cities by using the concept.